IMPROVING EARLY DIAGNOSIS AND TREATMENT OF ACUTE RHEUMATIC FEVER IN CHILDREN - Kuldashev Sardor Furqatovich (Scholar Express Journals, 2023)
Despite significant progress in disease reduction, acute rheumatic fever (ARF) has been observed in many countries of the world in recent decades. Determining the course of the disease requires a complete analysis of clinical, laboratory and instrumental data and is very important for timely diagnosis
Keywords: acute rheumatic fever; criteria Kiselya; Jones